2014
DOI: 10.3168/jds.2013-7762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whey concentration on protein recovery in fresh ovine ricotta cheese

Abstract: Ricotta cheese, particularly the ovine type, is a typical Italian dairy product obtained by heat-coagulation of the proteins in whey. The aim of this work was to investigate the influence of whey protein concentration, obtained by ultrafiltration, on yield of fresh ovine ricotta cheese. Ricotta cheeses were obtained by thermocoagulation of mixtures with protein content of 1.56, 3.10, 4.16, and 7.09g/100g from the mixing of skim whey and ultrafiltered skim whey. A fat-to-protein ratio of 1.1 (wt/wt) was obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 31 publications
4
31
0
1
Order By: Relevance
“…Cheese quality scores immediately after both treatments were slightly lower than for control samples, because panelists detected some off-odors. This off-odor perception in samples treated with UV-C could be attributed to photo-induced changes, e.g., photo reactivity of proteins, which was also attested previously [22], being ricotta a food very rich in amino acids [33]. For NUV-vis-treated samples, these detected off-odors may be due to the fact that sample exposure for 400 second would increase the surface temperature, thus affecting the product characteristics and in particular the smell perceived just after the treatment [34].…”
Section: Shelf Life Study Of Ricotta Cheese Treated With Uv-c and Nuvsupporting
confidence: 68%
“…Cheese quality scores immediately after both treatments were slightly lower than for control samples, because panelists detected some off-odors. This off-odor perception in samples treated with UV-C could be attributed to photo-induced changes, e.g., photo reactivity of proteins, which was also attested previously [22], being ricotta a food very rich in amino acids [33]. For NUV-vis-treated samples, these detected off-odors may be due to the fact that sample exposure for 400 second would increase the surface temperature, thus affecting the product characteristics and in particular the smell perceived just after the treatment [34].…”
Section: Shelf Life Study Of Ricotta Cheese Treated With Uv-c and Nuvsupporting
confidence: 68%
“…However, nitrogen in serum consists mainly of non-protein nitrogen and true proteins are mainly proteose-peptones, which are heat-resistant (Walstra and Jenness, 1984) and remain soluble by heating the whey during the cheese-making process, and fine casein granules which were not incorporated in the cheeses during drainage. Salvatore et al (2014) reported that the crude protein content of serum after the manufacture of Ricotta cheese was about 1%, which was similar to that in our experiments.…”
Section: Sensory Characteristicssupporting
confidence: 91%
“…The characteristics of pH 5.2 F suggest a higher moisture loss in ricotta cheese B than in A during the process. Salvatore et al [32] indicated that a statistically significant lower moisture content value was observed from the ricotta cheese with a lower protein content, likely due to the water-binding capacity of denatured whey proteins.…”
Section: Gross Composition Of Ricotta Cheese Made From Goat Milk and mentioning
confidence: 99%